El régimen hidrológico del río Cinca a finales del siglo XIX - Galván Plaza, R. (Geographicalia, 2016)
The 1911 "Riegos del Alto Aragón" project, includes in its 6"’ annex several stream flow data from different rivers, which are quoted as official data from the extinct "División Hidráulica del Ebro". Among them there is a 9-year period of flow rate from the Cinca river at the confluence site with the Ebro river, corresponding to the period 1881-1894. These forgotten data, are one of the most old systematic flow gauging we know in the Ebro basin, so it is an inestimable document for the description of the hydrologic regime of one of its main tributaries in those far years and its evolution to its present status, both for natural causes and for the intense human development during the XX century. Besides, bringing to life these data has interest for future studies of climatic and morphologic evolution, in spite of the lack of accuracy that the data analysis has proved.